A scoping review of type 2 diabetes mellitus in Pakistan investigating the status of glycemic control, awareness, treatment adherence, complications and cost - Taimur, Hira; Ahmad, Ishtiaq; Khan, Hamza; Shirayama, Yoshihisa; Okamoto, Miyoko; Aung, Myo Nyein; Shabbir, Sameera; Yuasa, Motoyuki (Frontiers in Endocrinology, 2024)
The high prevalence of Type 2 diabetes mellitus(T2DM) in Pakistan is a challenge to the existing healthcare system. This is the first comprehensive review of the status of glycemic control, diabetes knowledge, treatment adherence, complications and financial burden faced by the diabetic patient population of the country. Methods We searched PubMed, Web of Science and Scopus for studies on diabetes control, knowledge, treatment adherence, prevalence of complications and cost in Pakistan published in English from 2000 to 2024. We hand-searched Google Scholar for additional papers and included a total of 45 studies in our review. The review shows that poor glycemic control prevails among diabetic patients ranging from 44.7% to 86.4% along with half of the patients have poor diabetes knowledge (46.0% -70.0%). Treatment adherence level in diabetic patients varies widely in different studies, frequently reported complications are retinopathy (14.5%-43.0%), nephropathy (14.0%-31.0%) and neuropathy (10.8%-59.6%); and the disease poses a great deal of economic burden. Most of the studies were observational. Glycemic control and knowledge among individuals with T2DM in Pakistan are inadequate, leading to a high prevalence of complications that impose significant health and economic burdens. Further longitudinal studies generating evidence of lifestyle modifications as primary and secondary prevention strategies against diabetes in the Pakistani population can form a strong foundation for awareness campaigns and policy revisions.